PENGARUH KEBIASAAN BELAJAR DAN KONSENTRASI BELAJAR TERHADAP HASIL BELAJAR AKUNTANSI TERHADAP HASIL BELAJAR AKUNTANSI SISWA KELAS XI DI SMK NEGERI 1 PEMATANG SIANTAR T.A 2023/2024 - Elsa Marito; Sotarduga Sihombing; Herlina Hotmadinar Sianipar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Elsa Marito. NPM. 2001060085. This research aims to determine the influence of Study Habits and Study Concentration on the Accounting learning outcomes of Class XI students at SMK Negeri 1 Pematangsiantar T.A 2023/2024. This type of quantitative research has a research population of 100 students. The research sample consisted of 100 students. The sampling technique used is the non-probabilistic sampling technique. The sample used in this sample is a saturated sample. The data collection techniques used were questionnaires and tests on student learning outcomes using multiple choice questions with a total of 20 questions.The research results show that: 1) there is a positive and significant influence on student study habits on student accounting learning outcomes. This result can be seen in the t test where the calculated t value of study habits is 5.351 > t table value 1.665, which means this variable is significant. 2) there is a positive and significant influence of Learning Concentration on students' accounting learning outcomes. This result can be seen in the t test where the calculated t value of Learning Concentration is 14.77 > t table value of 1.665, which means this variable is significant. 3) Study habits and study concentration together influence the results. It can be seen in the calculated f test that the Sig F value is (0.026) smaller than the sig α value of 0.05. This indicates that the research results are rejected and accepted. Study Habits and Study Concentration influence the Accounting learning outcomes of class XI students at SMK Negeri 1 Pematangsiantar.